2010
DOI: 10.1007/s11104-010-0666-x
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic doses of boron in contrasting soils depend on soil water content

Abstract: Boron (B) affects plant growth in soil at B doses (mg added B kg -1 soil) that appear in the range of natural background B concentrations. A study was set up to determine B bioavailability by testing B toxicity to plant as affected by soil properties and ageing after soil dosing. Nineteen soils (pH 4.4-7.8) and 3 synthetic soils (sand-peat mixtures) were amended with 7 doses of H 3 BO 3 . Barley root elongation was determined immediately after B amendment and after 1 and 5 months ageing. Soil solution B concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…A decrease of 10% in barley root growth has been reported when soil solution boron concentration exceeded the -1 values between 16 and 59 mg l across different soils (Mertens et al, 2011). In the present study it appears that band application @ -1 5.0 and 7.5 kg ha caused high boron concentration in the root zone which led to higher boron uptake causing toxicity in the present study.…”
Section: Methodssupporting
confidence: 50%
“…A decrease of 10% in barley root growth has been reported when soil solution boron concentration exceeded the -1 values between 16 and 59 mg l across different soils (Mertens et al, 2011). In the present study it appears that band application @ -1 5.0 and 7.5 kg ha caused high boron concentration in the root zone which led to higher boron uptake causing toxicity in the present study.…”
Section: Methodssupporting
confidence: 50%
“…In addition, critical levels depend on soil type, pH, water status, texture, air humidity and temperature, plant species, and genotype [127,144]. For example, it was found that boron concentrations exhibiting toxic effects on barley (root growth reduction by 10%) varied about 10-fold among 22 tested soils differing in pH, texture, and percentage of organic matter [145].…”
Section: Soil Boronmentioning
confidence: 99%
“…B absorbed by roots is transported via xylem, mostly driven by plant transpiration, and then distributed to all plant tissues (Huang et al 2005;Mertens et al 2011;Wimmer and Eichert 2013;Mesquita et al 2016). However, this nutrient exhibits low mobility in the phloem of citrus (Boaretto et al 2008) and, consequently, limited redistribution in the trees (Liu et al 2012).…”
Section: Introductionmentioning
confidence: 99%